[62] The mystery of gross haematuria in a patient on leflunomide: A case report and literature review - Vincent Khor (Taylor & Francis Group, 2018)
Objective: To report a case of gross haematuria in a patient on leflunomide. In 1998, the USA Food and Drug Administration approved leflunomide for the treatment of active rheumatoid arthritis. Leflunomide is classified as a disease-modifying anti-rheumatic drug (DMARD), which has immunomodulatory, anti-inflammatory, analgesics, and antipyretic effects. Methods: We report an atypical case of a 70-year-old woman who presented with two isolated episodes of gross haematuria with mild thrombocytopaenia, 5 months after she was started on leflunomide. Cystoscopy showed an abnormal bladder neovascularisation pattern with bleeding from one of the small vessels. Based on the timeline and clinical course, we hypothesised that the gross haematuria and neovascularisation was associated with the use of leflunomide. An electronic search of PubMed/MEDLINE was performed with the text words ‘Leflunomide’, ‘haematuria’, ‘angiogenesis’, ‘neovascularization’, and ‘DMARD’. The relevant articles were selected for review. Results: The literature review revealed one report of gross haematuria that was associated with leflunomide, and this was due to its interaction with warfarin. There were no reports that related to an abnormal bladder neovascularisation with leflunomide as seen in our case. She presented with two episodes of gross haematuria after she was started on leflunomide and presented to our hospital on her second episode. The second episode of gross haematuria was severe, which required blood transfusions, multiple manual bladder washouts, and cystodiathermy in the operating theatre. Rigid cystoscopy showed an abnormal neovascularisation pattern throughout the bladder. The haematuria stopped subsequently. The thrombocytopaenia improved, and haematuria did not recur after the cessation of leflunomide. A follow-up cystoscopy 3 months later showed a similar neovascularisation pattern with no active bleeding. Conclusion: The literature shows that leflunomide has anti-proliferative and anti-angiogenesis activities. To the best of our knowledge, we have not been able find a reasonable explanation for the observed bladder neovascularisation pattern and its association with DMARD, particularly leflunomide.